The Wiley‐Blackwell Handbook of Family Psychology 2009
DOI: 10.1002/9781444310238.ch50
|View full text |Cite
|
Sign up to set email alerts
|

Family Forensic Psychology

Abstract: Family forensic psychology (FFP) is an area of specialized psychological practice that lies at the intersection of family psychology, forensic psychology, and the legal system. It is a notably challenging area of practice that encompasses specialized intervention, evaluation, and consultation. This chapter provides a general overview of the field of FFP focused into two areas. First, we will introduce the practice of forensic psychology and describe elements that differentiate forensic practice from general cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…CFP practice encompasses subspecialty areas that require additional education and supervised training, namely, family forensic psychology (FFP; Welsh, Greenberg, & Graham-Howard, 2009), systemic substance use treatment (Stanton, 2009b), and systemic sex therapy . FFP integrates the knowledge and skills of two specialties of professional psychology-CFP and forensic psychology-to serve families involved with the justice system.…”
Section: Practice Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…CFP practice encompasses subspecialty areas that require additional education and supervised training, namely, family forensic psychology (FFP; Welsh, Greenberg, & Graham-Howard, 2009), systemic substance use treatment (Stanton, 2009b), and systemic sex therapy . FFP integrates the knowledge and skills of two specialties of professional psychology-CFP and forensic psychology-to serve families involved with the justice system.…”
Section: Practice Activitiesmentioning
confidence: 99%
“…FFP integrates the knowledge and skills of two specialties of professional psychology-CFP and forensic psychology-to serve families involved with the justice system. FFP activities include specialized interventions, such as mediation and parent coordination, expert consultation and testimony in child custody disputes, and forensic evaluation in child custody and juvenile delinquency cases (Welsh et al, 2009). Systemic treatment for substance use disorders and systemic sex therapy are special practice applications of CFP discussed in the next section.…”
Section: Practice Activitiesmentioning
confidence: 99%
“…Many different circumstances may lead to families' involvement with the legal system. Various authors have identified overlapping areas of interest among family psychology and family law, juvenile dependency (child abuse) and juvenile delinquency law, elder law, and other specialties (Grossman & Okun, 2003;Kaslow, 2000;Welsh, Greenberg, & Graham-Howard, 2009). FFPs may provide services including assessment, treatment and other interventions, parent coordination, consultation, mediation, expert testimony, and other services.…”
Section: Family Forensic Psychologymentioning
confidence: 99%
“…Family forensic psychologists provide expertise to the legal system. (p. 165) Welsh et al (2009) expanded on that definition to note that FFP is a specialized application of family psychology and forensic psychology (including elements of both) that provides expert-level services to families involved with the legal system, their attorneys, and the courts. These services may include intervention or direct services to families, forensic evaluation, consultation, research, expert testimony, parenting coordination, specialized therapy or parenting education, or other services.…”
Section: Forensic Psychology and Family Forensic Psychology: Adjustin...mentioning
confidence: 99%
See 1 more Smart Citation